Successive generation introduction time for high technological products: an analysis based on different multi-attribute utility functions - David Hughes (Environment, Development and Sustainability, 2022)
Highly competitive markets have forced many organizations to come up with generational products. The relevance, appropriateness, added functionality, and sustainability are some of the potential reasons behind the launch of a new generation over the previous generation. The launch time of the new generation is dependent on the performance of the existing generation in the market which can be measured based on the attributes viz. the adoption behavior of the customer and indicator of adoption rate. The introduction of a new generation greatly affects the market of the existing generation of the product and huge capital is ought to be invested in feature enhancement in the latest generation as compared to the existing version. Consequently, the investment made in production and marketing activities should be economical which significantly influences the launch time. Based on these attributes, the focus is on determining the launch time of the successive generation of the product. In this paper, three conflicting and contrasting attributes: customer adoption behavior, adoption rate indicator, and cost are proposed. The aim is to study and understand the impact of the trade-off for these attributes on the launch time of successive generations of the product. To examine the tradeoff between these attributes, multi-attribute utility theory has been used. The proposed decision approach is based on three different weighted combinations of the utility function in multi-attribute utility theory. Additionally, three different forms of utility functions viz, the weighted arithmetic, geometric and harmonic forms have been used in understanding their superiority over one another. For validation purposes, the case in which an organization launches successive generations of a durable product for which demand is characterized by an innovation diffusion process has been assessed.